Aesthetic Modification of Room Impulse Responses for Interactive Auralization - Godin, Keith; Gamper, Hannes; Raghuvanshi, Nikunj (AES International Conference on Immersive and Interactive Audio, 2019)
Interactive auralization workflows in games and virtual reality today employ manual markup coupled to designer-specified acoustic effects that lack spatial detail. Acoustic simulation can model such detail, yet is uncommon because realism often does not perfectly align with aesthetic goals. We show how to integrate realistic acoustic simulation while retaining designer control over aesthetics. Our method eliminates manual zone placement, provides spatially smooth transitions, and automates re-design for scene changes. It proceeds by computing perceptual parameters from simulated impulse responses, then applying transformations based on novel modification controls presented to the user. The result is an end-to-end physics-based auralization system with designer control. We present case studies that show the viability of such an approach.